2014
DOI: 10.1089/neu.2013.3108
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Drug Tamoxifen: A Potential Therapeutic Treatment for Spinal Cord Injury

Abstract: Tamoxifen (TMX) is a selective estrogen receptor modulator that can mimic the neuroprotective effects of estrogen but lacks its systemic adverse effects. We found that TMX (1 mg/day) significantly improved the motor recovery of partially paralyzed hind limbs of male adult rats with thoracic spinal cord injury (SCI), thus indicating a translational potential for this cancer medication given its clinical safety and applicability and the lack of currently available treatments for SCI. To shed light on the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 71 publications
(78 reference statements)
2
31
1
Order By: Relevance
“…14 The acute behavioral locomotor recovery (7 DPI) observed in our studies is different from that obtained by Guptarak and colleagues, 14 which observed a recovery at 14 DPI up to the end time point of 35 DPI. The discrepancy may be related to the sex of the animals used in each study and the lesion produced by the impactors used in each research project (NYU/MASCIS versus Infinite Horizon impactor).…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…14 The acute behavioral locomotor recovery (7 DPI) observed in our studies is different from that obtained by Guptarak and colleagues, 14 which observed a recovery at 14 DPI up to the end time point of 35 DPI. The discrepancy may be related to the sex of the animals used in each study and the lesion produced by the impactors used in each research project (NYU/MASCIS versus Infinite Horizon impactor).…”
Section: Discussioncontrasting
confidence: 92%
“…One-way analysis of variance Tukey's multiple comparison test (**p < 0.01), data are mean -SEM, sham (PLB+TAM) n = 9, SCI PLB (rats from t = 0 h + 24 h) n = 4, SCI TAM 0 h n = 3, SCI TAM 24 h n = 3. recovery in the chronic phase of the injury (between 14 and 35 DPI) in male rats. 14 Our results confirmed the behavioral observations obtained by these two groups, but expanded the information to the inclusion of female animals in our studies and extended the therapeutic window up to 24 h versus the previously reported up to 2 h after SCI.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations